Prenatal diagnosis of partial monosomy 5p (5p15.1→pter) and partial trisomy 7p (7p15.2→pter) associated with cystic hygroma, abnormal skull development, and ventriculomegaly - Chih-Ping Chen; Liang-Kai Wang; Schu-Rern Chern; Peih-Shan Wu; Kevin Ko; Yen-Ni Chen; Shin-Wen Chen; Meng-Shan Lee; Wayseen Wang (Taiwanese Journal of Obstetrics & Gynecology, 2016)
Objective: Prenatal diagnosis of concomitant chromosome 5p deletion syndrome and chromosome 7p duplication syndrome in a fetus with abnormal prenatal ultrasound is presented. Case Report: A 34-year-old woman was referred for amniocentesis at 22 weeks of gestation because of an irregular-shaped skull, bilateral ventriculomegaly, and nuchal cystic hygroma. Amniocentesis revealed a derivative chromosome 5 with a distal 5p deletion and an addendum of an extra unknown chromosomal segment at the breakpoint of 5p. Cytogenetic analysis of parental bloods revealed a karyotype of 46, XX, t(5;7)(p15.1;p15.2) in the mother and a karyotype of 46,XY in the father. The karyotype of the fetus was 46, XX, der(5) t(5;7)(p15.1;p15.2)mat consistent with partial monosomy 5p (5p15.1→pter) and partial trisomy 7p (7p15.2→pter). A malformed fetus was subsequently delivered with an irregular-shaped skull, a large anterior fontanelle, brachycephaly, hypertelorism, a high and prominent forehead, a large nuchal cystic hygroma, large low-set ears, a short and flattened nose, and micrognathia. Array comparative genomic hybridization analysis of the placenta revealed the result of arr 5p15.33p15.1 (22,179-18,133,327)×1.0, 7p22.3p15.2 (54,215-25,551,540)×3.0, indicating an 18.11-Mb deletion of 5p (5p15.33-p15.1) and a 22.5-Mb duplication of 7p (7p22.3-p15.2). Cord blood sampling revealed a karyotype of 46, XX, der(5)t(5;7) (p15.1;p15.2)mat. Conclusion: Fetuses with 5p deletion syndrome and 7p duplication syndrome may present ventriculomegaly, abnormal skull development, and cystic hygroma on prenatal ultrasound.